Experimental study and CFD numerical simulation of an innovative vapor splitter in dividing wall column. Issue 8 (22nd May 2020) - Li, Chunli; Li, Jingyu; Li, Dongchuan; Ma, Shuaiming; Li, Hao
Abstract: The vapor split ratio (RV ) adjustment plays an important role on energy efficiency during dividing wall column (DWC) operation. In order to achieve active control of R V, this aticle presents an innovative vapor splitter driven by hydraulics. The vapor flows into main tower from prefractionation section through the rectangle hole located at the end of the partition. Vapor splitting is implemented by the change of flow resistance at the rectangular hole caused by adjusting the liquid level on the bottom plate. This design makes full use of the hydraulic properties in DWC, employing simpler construction with single tunable parameter. Numerical simulations and laboratory tests were both carried out to validate its performance in the DWC with a diameter of 600 mm. The results demonstrate that the desired R V can be handled effectively in the approximate range from 0.5 to 2, basically satisfying the industrial demand for the gas distribution.